Targeting Macrophage Migration Inhibitory Factor in Acute Pancreatitis and Pancreatic Cancer - Wen, Yongjian; Cai, Wenhao; Yang, Jingyu; Fu, Xianghui; Putha, Lohitha; Xia, Qing; Windsor, John A.; Phillips, Anthony R.; Tyndall, Joel D. A.; Du, Dan; Liu, Tingting; Huang, Wei (Frontiers in Pharmacology, 2021)
Macrophage migration inhibitory factor (MIF) is a pleiotropic cytokine implicated in the pathogenesis of inflammation and cancer. It is produced by various cells and circulating MIF has been identified as a biomarker for a range of diseases. Extracellular MIF mainly binds to the cluster of differentiation 74 (CD74)/CD44 to activate downstream signalling pathways. These in turn activate immune responses, enhance inflammation and can promote cancer cell proliferation and invasion. Extracellular MIF also binds to the C-X-C chemokine receptors cooperating with or without CD74 to activate chemokine response. Intracellular MIF is involved in Toll-like receptor and inflammasome-mediated inflammatory response. Pharmacological inhibition of MIF has also been shown to hold great promise in treating inflammatory diseases and cancer, including small molecule MIF inhibitors targeting the tautomerase active site of MIF and antibodies that neutralise MIF. In the current review, we discuss the role of MIF in inflammation-related signalling pathways and summarise the recent advances of the role of MIF in experimental and clinical exocrine pancreatic diseases. We expect to provide insights into clinical translation of MIF antagonism as a strategy for treating acute pancreatitis and pancreatic cancer.